Synthetic lethal targeting of PTEN mutant cells with PARP inhibitors - Mendes-Pereira, Ana M (WILEY-VCH Verlag, 2009)
The tumour suppressor gene, phosphatase and tensin homolog (PTEN), is one of the most commonly mutated genes in human cancers. Recent evidence suggests that PTEN is important for the maintenance of genome stability. Here, we show that PTEN deficiency causes a homologous recombination (HR) defect in human tumour cells. The HR deficiency caused by PTEN deficiency, sensitizes tumour cells to potent inhibitors of the DNA repair enzyme poly(ADP-ribose) polymerase (PARP), both in vitro and in vivo. PARP inhibitors are now showing considerable promise in the clinic, specifically in patients with mutations in either of the breast cancer susceptibility genes BRCA1 or BRCA2. The data we present here now suggests that the clinical assessment of PARP inhibitors should be extended beyond those with BRCA mutations to a larger group of patients with PTEN mutant tumours.